Comparison of Surgically Induced Astigmatism L-Shaped vs Straight Incisions in Manual Small Incision Cataract Surgery - Rohini Choudhary; Uzma Choudhary; Ashish Sawhney Sawhney (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Aims and objective: To compare surgically induced astigmatism(SIA) in L-shaped vs straight incision in manual small incision cataract surgery(SICS). Material method: 60 patients aged 35 years and above with uncomplicated cataract with nuclear sclerosis of any grade were included in the study who were divided into 2 groups randomly. 30 patients underwent SICS with straight scleral incision and 30 with L-shaped incision. Data was analyzed using SPSS version 15.0 statistical analysis and calculations were performed using SIA calculator version 2.1. Results: The SIA (surgically induced astigmatism) was 1.14 ± 0.44D, 0.81 ± 0.40D, 0.61 ± 0.33 D on 1st post-operative day, 4 weeks and 6 weeks respectively in straight incision group and the SIA was 0.79 ± 0.36D, 0.33 ± 0.31D, 0.15 ± 0.18D on 1st post-operative day, 4 weeks and 6 weeks respectively in L-shaped incision group. Conclusion: L-shaped incision technique induces less amount of SIA as compared to straight incision and the difference is statistically significant. Also, L-shaped incision maintains better anterior chamber stability and leads to early visual rehabilitation. In poor and developing countries where still majority of cases are being operated by manual SICS, achieving emmetropia or minimal refractive errors should be the goal.